Drivers of Dashboard Development (3-D): A Curricular Continuous Quality Improvement Approach. (April 2016) - Shroyer, A. Laurie; Lu, Wei-Hsin; Chandran, Latha
Abstract : Problem: Undergraduate medical education (UME) programs are seeking systematic ways to monitor and manage their educational performance metrics and document their achievement of external goals (e.g., Liaison Committee on Medical Education [LCME] accreditation requirements) and internal objectives (institution-specific metrics). In other continuous quality improvement (CQI) settings, summary dashboard reports have been used to evaluate and improve performance. Approach: The Stony Brook University School of Medicine UME leadership team developed and implemented summary dashboard performance reports in 2009 to document LCME standards/criteria compliance, evaluate medical student performance, and identify progress in attaining institutional curricular goals and objectives. Key performance indicators (KPIs) and benchmarks were established and have been routinely monitored as part of the novel Drivers of Dashboard Development (3-D) approach to curricular CQI. Outcomes: The systematic 3-D approach has had positive CQI impacts. Substantial improvements over time have been documented in KPIs including timeliness of clerkship grades, midclerkship feedback, student mistreatment policy awareness, and student satisfaction. Stakeholder feedback indicates that the dashboards have provided useful information guiding data-driven curricular changes, such as integrating clinician–scientists as lecturers in basic science courses to clarify the clinical relevance of specific topics. Gaining stakeholder acceptance of the 3-D approach required clear communication of preestablished targets and annual meetings with department leaders and course/clerkship directors. Next Steps: The 3-D approach may be considered by UME programs as a template for providing faculty and leadership with a CQI framework to establish shared goals, document compliance, report accomplishments, enrich communications, facilitate decisions, and improve performance.